Environmental perception, pro-environmental behaviours and quality of life of residents of Perequê Beach - Oliveira-Monteiro, Nancy Ramacciotti de; Costa, Ana Júlia Pereira; Araújo, Fernanda Ribeiro de; Castro, Ítalo Braga de (Sustainability in Debate, 2024)
Praia do Perequê is located in the city of Guarujá (SP) and presents a situation of severe socio- environmental impacts directly linked to tourism and navigation activities. This research aimed to assess environmental perception, pro-environmental behaviours and quality of life of the caiçara community living in this region. Adult and elderly residents of Perequê Beach responded to the Environmental Perception Questionnaire – Beach; Ecological Behaviour Scale, WHOQOL-bref and Brazil Economic Classification Criteria in public places. Results indicated elements of positive environmental perception interacting with socioeconomic difficulties perception (in transportation and public health care), waste disposal behaviours carried out by residents and problems in the environmental domain of quality of life. This initiative will guide the actions to be undertaken by the municipal management of Guarujá.